The Effect of the Group Investigation Learning Model Assisted by Digital Mind Map (GI-DMM) on the Learning Outcomes Students in the Affective Domain - Delnanda, Afadia; Rosba, Evrialiani; Maizeli, Annika (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
The learning process carried out by teachers does not actively involve students, this is because the learning models and media applied by teachers have not been implemented optimally. Based on these problems, the right solution is needed by applying a learning model that can activate students. One of them is by applying the Group Investigation learning model assisted by Digital Mind Map (GI-DMM). The aim of the research was to find out the effect the Group Investigation model learning assisted by Digital Mind Map (GI-DMM) to the learning outcomes of students' affective domains. This research method is a true experiment with a Randomized Control Group Posttest Only Design research design. The population in this study were all of class X IPA. Sampling was carried out by purposive sampling technique by means of a lot system, experimental class and control class. The research instrument for the affective domain was in the form of observation sheets for students' attitudes during the learning process. Data analysis techniques used hypothesis testing (t-test). The results of the study in the affective domain of the experimental class obtained an average value of 93.00 and that of the control class was 88.53. Thus it can be concluded that through the application of the Digital Mind Map-assisted Group Investigation Model (GI-DMM) it can improve learning outcomes in the affective domain of students.